Electrocardiographic right ventricular strain precedes hypoxic pulseless electrical activity cardiac arrests: Looking beyond pulmonary embolism. (June 2020) - Do, Duc H.; Yang, Jason J.; Kuo, Alan; Bradfield, Jason S.; Hu, Xiao; Shivkumar, Kalyanam; Boyle, Noel G.
Abstract: Aim: The role of the right ventricle (RV) in pulseless electrical activity (PEA) is poorly defined outside of pulmonary embolism. We aimed to (1) describe the continuous electrocardiographic (ECG) manifestations of RV strain (RVS) preceding PEA/Asystole in-hospital cardiac arrest (IHCA), and (2) determine the prevalence and clinical causes of RVS in PEA/Asystole IHCA. Methods: In this retrospective cross-sectional study, we evaluated 140 patients with continuous ECG data preceding PEA/Asystole IHCA. We iteratively defined the RVS continuous ECG pattern using the development cohort (93 patients). Clinical cause determination was blinded from ECG analysis in the validation cohort (47 patients). Results: The overall cohort had mean age 62.1 ± 17.1 years, 70% return of spontaneous circulation and 30% survival to discharge. RVS continuous ECG pattern was defined as progressive RV depolarization delay in lead V1 with at least one supporting finding of RV ischaemia or right axis deviation. Using this criterion, 66/140 (47%) cases showed preceding RVS. In patients with RVS, no pulmonary embolism was found in 9/13 (69%) autopsies and 8/10 (80%) CT chest angiograms. The positive and negative predictive value of RVS pattern for diagnosing a respiratory cause of PEA/Asystole in the validation cohort was 81% [95% CI 64–98%] and 58% [95% CI 36–81%], respectively. Conclusion: RVS continuous ECG pattern preceded 47% of PEA/Asystole IHCA and is predictive of a respiratory cause of cardiac arrest, not just pulmonary embolism. These suggest that rapid elevations in pulmonary pressures and resultant RV failure may cause PEA in respiratory failure.